Multistep DNA-templated reactions for the synthesis of functional sequence controlled oligomers. - Mckee, M; Milnes, P; Bath, J; Stulz, E; Turberfield, A; O'Reilly, R (2010)
Biomimetic: A strand displacement mechanism was designed to permit DNA-templated synthesis of functional oligomers of arbitrary length (see scheme). Key features of the mechanism are that successive coupling reactions take place in near-identical environments and that purification is only necessary in the last synthesis step. © 2010 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.